Polycyclic Aromatic Hydrocarbons: Sources, Toxicity, and Remediation Approaches - Patel, Avani Bharatkumar; Shaikh, Shabnam; Jain, Kunal R.; Desai, Chirayu; Madamwar, Datta (Frontiers in Microbiology, 2020)
Polycyclic aromatic hydrocarbons (PAHs) are wide-spread across the globe, mainly due to long-term anthropogenic sources of pollution. The inherent properties of PAHs such as hetero-cyclic aromatic ring structures, hydrophobicity and thermostability have made them recalcitrant and highly persistent in the environment. PAH pollutants have been determined to be highly toxic, mutagenic, carcinogenic, teratogenic and immunotoxicogenic to various life forms. Therefore, this review discusses the primary sources of PAHs emissions, exposure routes and their toxic effects on humans, in particular. This review briefly summarizes the physical and chemical PAH remediation approaches such as membrane filtration, soil washing, adsorption, electrokinetic, thermal, oxidation and photocatalytic treatments. This review provides a detailed systematic compilation of the eco-friendly biological treatment solutions for remediation of PAHs such as microbial remediation approaches using bacteria, archaea, fungi, algae and co-cultures. In situ and ex-situ biological treatments such as land farming, biostimulation, bioaugmentation, phytoremediation, bioreactor vermiremediation approaches are discussed in detail and a summary of the factors affecting and limiting PAH bioremediation are also discussed. An overview of newly emerging technologies employing multi-process combinatorial treatment approaches and newer concepts on generation of value-added by products during PAH remediation is highlighted in this review.